THE INFLUENCE OF EMPLOYER ATTRACTIVENESS, WORK–LIFE BALANCE, AND ORGANIZATIONAL REPUTATION ON JOB SATISFACTION AMONG HEALTHCARE WORKERS: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - David William Brian Iskandar (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to determine the effect of employer attractiveness, work–life balance, and organizational reputation on job satisfaction among healthcare workers, with organizational commitment as a mediating variable. This study employs a quantitative approach with a correlational research design. The population in this study consists of all healthcare workers employed at Hospital X, including doctors, nurses, midwives, pharmacists, and other medical support staff. The sampling technique used in this study is total sampling. The total sample comprises 100 healthcare workers at Hospital X. The data analysis technique utilized is Structural Equation Modeling (SEM) using Partial Least Squares (PLS). Based on the results of the study, employer attractiveness, work–life balance, and organizational reputation have a positive and significant effect on organizational commitment and job satisfaction among healthcare workers, while organizational commitment is able to mediate the influence of employer attractiveness, work–life balance, and organizational reputation on job satisfaction among healthcare workers. Future research is recommended to broaden the scope by incorporating additional variables such as leadership style, organizational culture, employee engagement, and psychological empowerment, as well as moderating factors like work motivation or emotional intelligence. Methodologically, future studies may adopt mixed-methods or longitudinal designs to gain deeper insights into healthcare workers’ perceptions over time. Expanding the research to include various hospitals and healthcare facilities is also suggested to enhance the generalizability and practical relevance of findings for human resource management in the healthcare sector.